In Vitro Culture of the Anxiolytic Plant, Souroubea Sympetala - Rojas Vargas, Alejandra (2020)
A protocol for the in vitro culture of the anxiolytic medicinal plant Souroubea sympetala (Marcgraviaceae) was developed, representing one of the first in vitro cultures for the family. This species was previously very difficult to cultivate from seed or cuttings. Methods included (1) the improvement of seed germination by axenic culture (2) development of regenerative cultures in vitro, then cultivation under greenhouse and finally field conditions and (3) creation of cell suspensions. Phytochemical analysis was undertaken by liquid chromatography coupled to mass spectrometry (HPLC-MS). The percentage of seed germination was improved from 2% to 59% in axenic culture and the full development of the seedling with its apical shoot and root took twenty-four days. The best seedling development was obtained in Gamborg B5 culture medium. Most friable callus formation, (66.7%) was obtained in the Murashige and Skoog medium supplemented with naphthalene acetic acid (1 mg · L–1) and kinetin (0.5 mg · L–1) from which viable cell cultures were developed. Analysis identified 4 main triterpenes with both in vitro plants and greenhouse grown plants derived from them. The triterpenes were betulinic acid, ursolic acid, alpha-amyrin and beta-amyrin. The betulinic acid found in greenhouse plants was comparable to wild plants. The cell suspension cultures had much lower levels of betulinic acid than plants and are not at present a viable source of this anxiolytic triterpene. In conclusion the method provides healthy plants for cultivation of this new medicinal plant and consequently harvesting of wild plants is not required.